Pemberdayaan Masyarakat PMKS oleh Pemerintah Kota Bandung 2022: Studi pada Dinas Sosial Kota Bandung - Janatun, Muthi; Rudiana, Rudiana (Penerbit Goodwood, 2023)
Purpose: Understanding the importance of social welfare is the primary basis for various government policies. Research methodology: This study analyzes the Empowerment Efforts for the welfare of PMKS Communities by the Bandung City Government in 2022 using descriptive and qualitative methods, with data obtained from field studies through interview observations. Results: The results showed that Empowerment Efforts for the welfare of PMKS Communities in Bandung City in 2022 showed that the main problem faced by the Bandung City Social Service was budget constraints. Social Service runs the PMKS empowerment program based on the APBD provided by the Bandung City Government. This budget determines the extent to which empowerment programs can be implemented. With limited budgets, the Social Services Office must allocate existing funds to various programs and activities, which often leads to limited coverage of training programs and the absence of follow-up assistance. Limitations: The Bandung City government's focus on social welfare includes concrete efforts to respond to the PMKS problem. Contribution: The results of this research can provide useful recommendations for the interests of the Bandung City Government.